Comparison of Rest to Aerobic Exercise and Placebo-like Treatment of Acute Sport-Related Concussion in Male and Female Adolescents - Willer, Barry S. (Arch Phys Med Rehabil, 2019)
OBJECTIVE: To compare a sample of adolescents with sport-related concussion (SRC) who were prescribed rest with 2 arms of a randomized controlled trial comparing aerobic exercise with placebo-like stretching. We also compared sex differences across the 3 approaches to treatment. DESIGN: Quasi-experimental trial. SETTING: University concussion management clinics. PARTICIPANTS: Adolescent athletes (aged 13-18 years) presenting within 10 days of SRC (mean, 5 days after injury) received a recommendation for rest (rest group [RG], n=48, 15.4±1y, 25% female). Their outcomes were compared with matched samples of adolescents assigned to aerobic exercise (exercise group [EG], n=52, 15.3±2y, 46% female) or placebo-like stretching (placebo group [PG], n=51, 15.4±2y, 47% female) (N=151). MAIN OUTCOME MEASURES: The primary outcome was median days from injury to recovery. The secondary outcome was proportion classified as normal recovery (<30d) or delayed recovery (≥30d). RESULTS: The RG recovered in 16 days (interquartile range, 9.25-23.25d), which was significantly delayed (P=.020) compared with EG (13d; interquartile range, 10-18.5d). The PG recovered in 17 days (interquartile range, 13-23d). Four percent of the EG, 14% of the PG, and 13% of the RG had delayed recovery (P=.190). There was no difference in recovery time or delayed recovery between male participants and female participants across groups. Female participants prescribed rest experienced an increase in symptoms vs the other groups (P=.013). CONCLUSION: Relative rest and a placebo-like stretching program were very similar in days to recovery and symptom improvement pattern after SRC. Both conditions were less effective than subsymptom threshold aerobic exercise. Female adolescents appear to be susceptible to symptom increase when prescribed rest.